Challenges in Microgrids with Medium Voltage Circuit - Hércules A. Oliveira; Luiza H. S. Santos; Luiz A. de S. Ribeiro; José G. de Matos; Lucas de P. A. Pinheiro (Eletrônica de Potência)
This paper presents and discusses challenges in microgrids (uGrid) that arise when they operate isolated from the main grid. Specifically, these challenges occur because the system becomes an ungrounded delta configuration, and the microgrid power sources exhibit low short-circuit capacity. The important issues addressed include the failure to detect ground overcurrent during an earth fault event, voltage imbalances recorded by voltage transformers (VTs) connected between phases and earth, and the phenomenon of ferroresonance. These issues directly impact the coordination of electrical protection, component integrity, and synchronization checks between different power sources within the uGrid. Therefore, the Energy Management System (EMS) is tasked with managing protection devices and systematically responding to minimize disruptions, thereby ensuring operational security. This paper examines the protection functions within devices for both operational modes (on-grid and off-grid) and the corresponding decisions implemented as rules within the EMS. Effective coordination between protection devices and management systems ensures a rapid and selective response to faults, thereby enhancing microgrid security and facilitating efficient problem detection and resolution.